Public Attitude Transformations of Petropavlovsk-Kamchatka Citizens in March-September of 1917 - Ilina, Valentina Alexandrovna; Kamardina, Natalya Viktorovna (Journal of History Culture and Art Research, 2018)
This paper analyzes the changes in public attitude and political behavior of Petropavlovsk-Kamchatka city dwellers during the opening months of the Great Russian Revolution, with the writers paying especially close attention to the reasons and circumstances behind these changes. This research allows to define the specifics of public conscience transformation in the spring-summer of 1917 in the territories remoted from the main revolutionary front, as well as to plan further research concerning these matters. The paper clearly shows that the most far-away provinces of Russia were gradually getting involved in the revolution during the first half of 1917. This piece of work is written on the basis of both published and unpublished historical sources. A local newspaper titled “The Kamchatka News Letter”, which was the first printed newspaper in Kamchatka published from May 2, 1914 to spring of 1918, became the main source of historical information for the authors of this research.